Analysis of Receivables Control System in Avoiding Bad Debts at PT Pertamina Lubricants - Fachruddin, Wan; Putri Z, Fahreza; Br. Purba, Rahima (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2023)
This study aims to determine and evaluate the analysis of credit granting selection with the 5C principle, analyzing the turnover of accounts receivable and the implementation of the concept of an internal control system over accounts receivable at PT Pertamina Lubricants Sales Region I. The method used in this research uses descriptive qualitative research methods, namely by collecting and analyzing data, so as to provide a clear picture in accordance with the title that has been described. The data collection techniques used are interviews and documentation. The results of this study can explain that the 5C Application Analysis has been implemented properly. The important point that must be improved is a broader approach to the character of prospective debtors, such as seeking information from debtor relations. The turnover of trade receivables of PT Pertamina Lubricants is considered not optimal in managing its trade receivables because it is still below the set standard of 15 times while the average result of trade receivables is still 1.5 times, the author suggests that PT Pertamina Lubricants give awards in the form of incentives in stages based on the percentage of accounts receivable collection, giving these incentives can stimulate the enthusiasm of workers related to collecting trade receivables. For the results related to the Accounts Receivable Internal Control System at PT Pertamina Lubricants has been running well, where company management has implemented the basic concepts and principles of internal control according to COSO, but still requires some improvement. Improvements that need to be made include giving rewards to outsouching workers who help with operational administration if the billing goes smoothly and in accordance with company policy, on the other hand, giving punishment if the commitment to work does not go according to the company's vision and mission, carrying out the imposition of fines on customers according to the cooperation contract for the procurement of lubricants that have been mutually agreed upon and adding permanent human resources to the billing section so that there is no overlap of work / more focus according to the description of the responsibilities of each function worker.